Projected Utility of Pharmacogenomic Testing Among Individuals Hospitalized With COVID‐19: A Retrospective Multicenter Study in the United States - James M. Stevenson; G. Caleb Alexander; Natasha Palamuttam; Hemalkumar B. Mehta (Wiley, 2021)
Many academic institutions are collecting blood samples from patients seeking treatment for coronavirus disease 2019 (COVID‐19) to build research biorepositories. It may be feasible to extract pharmacogenomic (PGx) information from biorepositories for clinical use. We sought to characterize the potential value of multigene PGx testing among individuals hospitalized with COVID‐19 in the United States. We performed a cross‐sectional analysis of electronic health records from consecutive individuals hospitalized with COVID‐19 at a large, urban academic health system. We characterized medication orders, focusing on medications with actionable PGx guidance related to 14 commonly assayed genes (CYP2C19, CYP2C9, CYP2D6, CYP3A5, DPYD, G6PD, HLA‐A, HLA‐B, IFNL3, NUDT15, SLCO1B1, TPMT, UGT1A1, and VKORC1). A simulation analysis combined medication data with population phenotype frequencies to estimate how many treatment modifications would be enabled if multigene PGx results were available. Sixty‐four unique medications with PGx guidance were ordered at least once in the cohort (n = 1,852, mean age 60.1 years). Nearly nine in 10 individuals (89.7%) had at least one order for a medication with PGx guidance and 427 patients (23.1%) had orders for 4 or more actionable medications. Using a simulation, we estimated that 17 treatment modifications per 100 patients would be enabled if PGx results were available. The genes CYP2D6 and CYP2C19 were responsible for the majority of treatment modifications, and the medications most often affected were ondansetron, oxycodone, and clopidogrel. PGx results would be relevant for nearly all individuals hospitalized with COVID‐19 and would provide the opportunity to improve clinical care.